Magic angle of Sr_{2}RuO_{4}: Optimizing correlation-driven superconductivity - Jonas B. Profe; Luke C. Rhodes; Matteo Dürrnagel; Rebecca Bisset; Carolina A. Marques; Shun Chi; Tilman Schwemmer; Ronny Thomale; Dante M. Kennes; Chris A. Hooley; Peter Wahl (Physical Review Research)
Understanding of unconventional superconductivity is crucial for engineering materials with specific order parameters or elevated superconducting transition temperatures. However, for many materials, the pairing mechanism and symmetry of the order parameter remain unclear: reliable and efficient methods of predicting the order parameter and its response to tuning parameters are lacking. Here, we investigate the response of superconductivity in Sr_{2}RuO_{4} to structural distortions via the random phase approximation (RPA) and functional renormalization group (FRG), starting from realistic models of the electronic structure. Our results suggest that RPA misses the interplay of competing fluctuation channels. FRG reproduces key experimental findings. We predict a magic octahedral rotation angle, maximizing the superconducting T_{c} and a dominant d_{x^{2}−y^{2}} pairing symmetry. To enable experimental verification, we provide calculations of the phase-referenced Bogoliubov Quasiparticle Interference imaging. Our work demonstrates a designer approach to tuning unconventional superconductivity with relevance and applicability for a wide range of quantum materials.